Evaluation of an internet-based animated preparatory video for children undergoing non-sedated MRI - McGlashlan, Hannah L.; Dineen, Robert A.; Szeszak, Sofia; Whitehouse, William P.; Chow, Gabriel; Love, Andrew; Langmack, Gill; Wharrad, Heather (British Institute of Radiology, 2018)
Objectives: We evaluate the value of an internet-based educational animated video designed to prepare children for MRI scans, and whether this video reduces scan related anxiety in children with a neurological disorder, and healthy controls. Methods: Participants completed a pre- and post-sca questionnaire evaluating participant online viewing behaviour, understanding of the MRI procedure, anxiety regarding the MRI, impact of animation in preparing the child and whether the child’s expectation of the MRI scan matched their experience. Results: 21 children were recruited (12 healthy controls) ranging in age from 6.5 to 11.5 years. The animation was successfully accessed by participants on a range of digital devices and had high levels of approval. Children who viewed the animation had a good understanding of the MRI procedure and low anxiety levels prior to the scan, and reported that their expectations broadly matched the real-life MRI experience. Children reported that the animation positively impacted on their preparation with similar ratings before and after the scan, and the impact on preparation was rated greater by younger children. There were no group differences between healthy children and those with the neurological disorder for ratings of anxiety, impact on preparation and expectation of the experience. Conclusion: This evaluation demonstrates accessibility, acceptability and relevance of internet-based educational animation for typically developing children, and children with a neurodisability aged 6 to 11 years, with positive impact on preparation for MRI. Advances in knowledge: The internet-based educational animation provides a widely accessible tool to support preparation of children for non-sedated MRI.